Bioinspired Synthesis of ZnS Supraparticles toward Photoinduced Dechlorination of 2, 2′, 4, 4′, 5, 5′‐Hexachlorobiphenyl. Issue 8 (31st May 2013) - He, Liangcan; Xiong, Yansong; Zhao, Meiting; Mao, Xiang; Liu, Yaling; Zhao, Huijun; Tang, Zhiyong
<x xml:space="preserve">Abstract</x> All you need is a little inspiration: Inspired by nature, a green and low‐cost synthetic method was developed to prepare monodisperse ZnS supraparticles (SPs) with the zinc‐blende structure at 37.0 °C. The prepared ZnS SPs can be used as catalysts for the photoinduced dechlorination of 2, 2′, 4, 4′, 5, 5′‐hexachlorobiphenyl. A degradation efficiency of about 70 % was obtained under irradiation with UV light for 12 hours.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>